Retrospective phenology in western Mediterranean plants: revealing climate change patterns through herbarium specimens - Solakis Tena, Andros; Casimiro-Soriguer Solanas, Federico; Hidalgo-Triana, Noelia (Oxford University Press, 2025)
Herbarium specimens have proven useful for assessing phenological responses to climate change. Using preserved specimens, we analysed the changes in day of year (DOY) for four phenophases: three reproductive (preflowering, flowering, fruiting) and one vegetative (growth). We conducted phenological analysis across bioclimatic belts (thermotypes) from the Rivas–Martinez classification and across 77 taxa present in the Baetic Ranges of the southern Iberian Peninsula. Taxa were characteristic, common, or endemic species from Habitats of Community Interest (HCI) under the European Directive 92/43/EEC. Phenological shifts were assessed using two approaches: long-term trends in DOY with time and relationships with historical climate variables related to temperature and precipitation. At the thermotypes level, flowering advanced consistently over time and with increasing temperatures, showing homogeneous responses and suggesting a weakening of altitudinal differentiation. In contrast, growth exhibited thermotype-specific trends, with stronger advances at high elevations, while preflowering and fruiting showed little or no sensitivity to time or climate variables. At the species level, 31% of taxa showed phenological changes over time in the Baetic Ranges (−3.6 days/decade for reproductive and −5.6 days/decade for vegetative phenophases). However, 97% of taxa showed significant relationships with increasing temperatures and decreasing precipitation, particularly with mean annual temperature (−12.7 days for reproductive and −14.3 days for vegetative phenophases per increased °C). These phenological changes could hinder reproductive and vegetative success by causing mismatches with other ecosystem role-players. As the Mediterranean is expected to become warmer and drier, our findings indicate a potential threat to HCI in the southern Mediterranean.
Keywords: floración; fructificación; calentamiento global; Plantas -- Crecimiento; day of year (DOY); flowering; fruiting; global warming; growth; preserved specimen; thermotypes